Star Wars. Thrawn alliances - Zahn, Timothy; Houser, Jody (Marvel Worldwide, Inc., 2024)
"As rivals for the favor of the Emperor, Grand Admiral Thrawn and Darth Vader may seem like unlikely partners for a crucial mission! Yet this formidable twosome has worked together before. Years ago, Thrawn and the man once known as Anakin Skywalker were joined in the hunt for Padmé Amidala. Now, as each man carves his own way through the galaxy, they will find themselves bound together once more by the Emperor's will -- and they will be each be tested to their limits by an enemy worthy of their formidable combined might!"--Amazon.